Eye attack op art og kinetisk kunst : 1950-1970 - Jørgensen, Lærke Rydal; Holm, Michael Juul 1960-; Colstrup, Tine; Degel, Kirsten (Louisiana revy, 2016)
With the first major presentation of Op Art and Kinetic Art in Scandinavia for more than 50 years, Louisiana opens the door to a visual experimental laboratory with the whole range of media and techniques. 'Op Art' is an abbreviation of Optical Art and describes works which use ingeniously crafted optical illusions and effects that go straight to the core of our visual sensory apparatus. The movement had its inception in the middle of the 1950s and its glory days in the 1960s, when it established itself internationally across political and cultural contexts. The artists were preoccupied with science, the psychology of perception and the new technology of the time ? and turned their backs on old-fashioned storytelling and romantic sensitivity. While Kinetic and Optical Art originate from a particular time, the results are surprisingly timeless, and the movement has left striking marks in contemporary visual art and culture. The direct appeal to the senses is unabated ? and is effective today in a mixture of instant fascination and nostalgia.00With around 100 works and more than 40 artists, including Hungarian Victor Vasarely and English Bridget Riley in two of the main roles, the exhibition opens the door to a visual experimental laboratory with the whole range of media and techniques